COGNITIVE LEVEL IN READING QUESTION OF STUDENT'S BOOK "BAHASA INGGRIS" FOR TENTH GRADE OF SENIOR HIGH SCHOOL - Ainayah, Alya; Riza, Armilia; Yulmiati, Yulmiati (TELL - US JOURNAL, 2021)
This research was a descriptive research that aimed to analyze the cognitive level of reading questions in student’s book "Bahasa Inggris". Researcher analyzed the level of reading questions in the textbook based on the revised edition of Bloom’s Taxonomy. In the revision of Bloom’s Taxonomy there are 6 levels of question levels, namely: C1-Remembering, C2-Understanding, C3-Applying, C4- Analyzing, C5-Evaluating, and C6-Creating. The researcher used the textbook "Bahasa Inggris" as a source of data. The researcher used document checklist table in collected the data and analyzed the data to found the research findings. Researcher analyzed the questions only focused on reading questions in chapters of monologue text. After conducted the study, there were 7 chapters containing questions and there were 98 reading questions. The results showed that the level of questions contained in the textbook "Bahasa Inggris" only 5 levels. The results of the study, found the percentage of each level is 75.51% for remembering level, 9.18% for understanding level, 2.04% for applying level, 8.16% for analyzing, and 5.10% for evaluating. Of these, the most dominant level in the book is remembering with a percentage of 75.51%.